Type A bile leak secondary to distal common bile duct sludge following open conversion of acute cholecystitis - Khairilanuar, Norfarehah Binti (International Surgery Journal, 2025)
We report the case of a 68-year-old male who developed a suspected type A bile leak secondary to distal common bile duct (CBD) sludge following surgical management of acute cholecystitis in a rural hospital, Australia. The patient, who had multiple comorbidities and a BMI of 45, initially underwent laparoscopic cholecystectomy, which than converted to open due to dense adhesions and poor visualization. Persistent high bile output in the drain postoperatively prompted diagnostic laparoscopy and intraoperative cholangiography (IOC), revealing distal CBD sludge and confirming bile flow into the duodenum. The case highlighted the need for close postoperative monitoring and shows how IOC serves as a diagnostic tool to identify hidden biliary complications.